Acupotomy Treatment for Lumbar Disc Herniation - Chen Xilin; Fu Xinyi; Luo Zhichao; Xin Wenshan; Wang Quangui; Lee Mira; Guo Changqing (Journal of Acupuncture Research, 2020)
Background The aim of this study was to examine whether the effects of acupotomy therapy were beneficial for the treatment of protrusion of lumbar intervertebral disc. Methods The number of patients (n = 80) were equally assigned into treatment group and control group. Treatment group was given acupotomy therapy twice a week, and control group was given acupuncture 3 times a week, for 4 weeks. The beneficial effect and changes in score of the Japan Orthopedic Association (JOA) for low back pain were observed. Results Among 40 cases in the treatment group, there were 25 (62.5%) with an excellent effect, 13 (32.5%) with good effect, 1 (2.5%) with a medium effect and 1 (2.5%) with poor effect, with the total experiencing an excellent/good effect of 95.0%. Among 40 cases in the control group, there were 11 (27.5%) with an excellent effect, 17 (42.5%) with good effect, 10 (25.0%) with a medium effect, and 2 (5.0%) with poor effect, with an excellent/good rate of 70.0%. The result of the rank sum test showed Z = −4.923, p < 0.05 in the comparison, indicating a significantly better outcome following acupotomy compared with acupuncture. JOA scores increased in both groups after treatment (p < 0.05), which was more significant in the acupotomy treatment group (p < 0.05). Conclusion Acupotomy therapy has a beneficial effect on protrusion of lumbar intervertebral disc.